Exploring the relationship between frailty and executive dysfunction: the role of frontal white matter hyperintensities - Pozo, Natalia; Romero, César; Andrade, Maricarmen; Délano, Paul H.; Medel, Vicente; Troncoso, Marco; Orellana, Patricia; Rodriguez, Maria Isabel; Fabres, Camila; Delgado, Carolina (Frontiers in Aging Neuroscience, 2023)
Introduction Frailty is a geriatric syndrome frequently associated with executive dysfunction and white matter hyperintensities (WMH). But the relation between executive dysfunction and brain changes is poorly understood in frail subjects. Our hypothesis is that frontal-WMH mediates the association between frailty and executive dysfunction. Methods A convenience sample of 113 subjects older than 65 years without dementia was studied with neuropsychological test, a structured clinical interview, physical examination and brain MRI. They were classified as robust or pre-frail and frail using the frailty phenotype score (0–5). The frontal WMH (F-WMH) were manually graduated (0–6) using the “Age-Related White Matter Changes score” from FLAIR sequences at a 3 Tesla brain MRI. A mediation analysis was done for testing whether F-WMH could act as a link factor between frailty phenotype score and executive dysfunction. Results The group’s mean age was 74 ± 6 years, subjects with higher frailty score had more depressive symptoms and worse performance in executive function tests. A regression analysis that explained 52% of the variability in executive functions, revealed a significant direct effect of frailty score (Standardized βcoeff [95% CI] −0.201, [−0.319, −0.049], and F-WMH (−0.152[−0.269, −0.009]) on executive functions, while the F-WMH showed a small partial mediation effect between frailty and executive functions (−0.0395, [−0.09, −0.004]). Discussion Frontal matter hyperintensities had a small mediation effect on the association between frailty and executive dysfunction, suggesting that other neuropathological and neurofunctional changes might also be associated with executive dysfunction in frail subjects.